(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The symptomatology of Ulcerative Colitis (UC) presents from irregular, incomplete bowel evacuation to mucous and bloody defecation. Direct correlation of UC in Ayurvedic literature is not possible, may be correlated to Pittaja Atisara, Rakthaja Atisara, Kshataja Grahani, Samgrahini Grahani. This case report shows diagnosed case of Ulcerative Colitis with nidana (etiology), Samprapti (pathophysiology) and Rupa (clinical presentation) similar to Pittaja Atisara. Signs and symptoms observed were stools mixed with blood & mucous (Pita-Haridra-Saraktha-Sadavalaprabham), Udarashula (abdominal pain), Payusanthapa (burning sensation in anal region) and showed Rupa that of Pittaja Atisara. Treatment was given according treatment approach of Pittaja Atisara viz., Langhana, Pachana and Picha Vasthi. Initially patient general condition was worst, managed under the guidance of modern medicine consultation and gradually tapered to Ayurvedic medicines. Oral medicines chosen were based on Rakthasthambaka, Vranaropana, Agni deepana and Grahi action, the drugs used for Pichha vasti are Madhu, Charngeryadi ghritam, Murivenna, Yashtimadhu kalka, Shalmali kwatha. A 45-day course of treatment was given, during which 30 Picha Vasthi were administered, includes 14 days of solely Vasthi and the final 11 days of Samsarjana Kala. Treatment outcomes were evaluated using partial Mayo scores and through routine blood tests and colonoscopy. Partial Mayo score was evaluated at 0th, 15th, 30th, and 45th day of the treatment cycle. Total partial Mayo Index score went from Severe Disease (9) to Remission (1). Total Leucocyte Count (TLC) and indices for hemoglobin and RBC returned to normal range after treatment. The patient got improvement and Ayurveda treatment protocol was successful.